Polymeric microencapsulation of pequi oil: preparation and characterization - CASTELO, Rachel Menezes; da SILVA, Luana Carvalho; ALMEIDA, Herllan Vieira de; CHENG, Huai Nan; BISWAS, Atanu; MAGALHÃES, Hilton César Rodrigues; FURTADO, Roselayne Ferro (Food Science and Technology, 2024)
Microencapsulation is often used to protect an unstable bioactive ingredient from the actions of external factors. In our work, we have found biobased polymers to be particularly suited as polymeric microencapsulants. Thus, pequi oil (from Caryocar coriaceum) was encapsulated by ionic gelation through polyelectrolyte complex formation between chitosan and alginate. The process of microparticle formation was studied, and the formation of the polymeric emulsion and microparticles was fully characterized. The influence of freeze-drying and oven-drying on the characteristics of the microparticles was also investigated. The hydrophilic–lipophilic balance (HLB) was utilized as a testing protocol to prepare a stable emulsion for microencapsulation, with the HLB of 10.2 showing the best stability. The encapsulation efficiency and loading capacity were 96.2 and 37.0%, respectively. Oven-dried particles showed a smaller particle size and a lower degree of sphericity and swelling than freeze-dried particles. Furthermore, freeze-dried microparticles had a lower percentage of oleic acid than those dried in an oven. This systematic approach (involving preparation, characterization, and optimization) should be applicable to the polymeric microencapsulation of other unstable bioactive ingredients for food, cosmetic, and pharmaceutical applications.